Heritage proximity, attitudes to tourism impacts and residents’ support for heritage tourism in Kaole Site, Tanzania - Lwoga, Noel Biseko (Bulletin of Geography. Socio-economic Series, 2018)
This study examines determinants of residents’ support for tourism by testing a model based on the social exchange and material culture theories. The model proposes that perceptual heritage proximity influences residents’ attitudes to positive and negative impacts of tourism, which in turn influence residents’ support for tourism. The model was tested using data gathered from a sample of 256 local residents in Kaole Village, Tanzania. Results from structural equation modelling indicate that heritage proximity has an influence on attitudes to the impacts of tourism, which in turn influence support. The findings imply that heritage proximity serves as a point of reference for residents’ evaluation of tourism, which is critical in fostering support. Findings confirm the relevance of the heritage proximity concept in explaining support for tourism. The study provides recommendations to better engage the residents in tourism development. Suggestions for future research are provided.